SHEAR PERFORMANCE OF INTERNAL STIRRUPS AND EXTERNALLY BONDED CFRP ON RC BEAMS - KILIAN , LAU MEOW HING (2018)
The use of externally bonded FRP as a strengthening technique for RC structures is gaining popularity and interest during these last two decades.